Meningkatkan Prestasi Belajar Siswa dengan Model Kooperatif Learning Tipe Index Card Match pada Mata Pelajaran IPS - Supriyati, Supriyati (FKIP Unirow Tuban, 2022)
Schools as a place for the learning process have a very important position in the world of education. In the teaching and learning process, the teacher becomes a companion role in creating educative interactive situations, namely the interaction between teachers and students, students and students and learning resources and media in supporting the achievement of learning objectives. This study aims to determine the increase in student achievement in class VIII MTs Walisongo Kaliori Rembang for the 2019/2020 academic year. Based on the results of research and discussion, it is shown that the percentage of student learning outcomes who score with very high qualifications is 22.73% or as many as 5 students, high qualifications. by 63.64% or 14 students and students who get grades with moderate qualifications are 13.63% or as many as 3 students and the average value of learning outcomes is 85.68, so the percentage of students who achieve good qualifications has increased by 63, 89%, while the number of students who have not achieved good qualifications has decreased by 36.11%. From the results of this research and discussion, it can be concluded that: (1) Social studies learning activities through Cooperative Learning Type Index Card Match can improve the ability of class VIII MTs students Walisongo Kaliori Rembang for the 2019 / 2020 school year with good, (2) Improving the achievement of class VIII students at MTs Walisongo Kaliori Rembang for the 2019/2020 school year in the material of the Indonesian national movement in fighting for independence.